Management of Acute Primary Herpetic Gingivo-stomatitis in Children - Marzuqi, Naila; Taqwim, Ali; Vitasari, Niken Rahma; Saskianti, Tania (Indonesian Journal of Dental Medicine, 2019)
Background: Acute primary herpetic gingivostomatitis is the symptomatic presentation of the initial exposure to the herpes simplex virus 1 (HSV-1). The clinical condition of acute primary herpetic gingivostomatitis is characterized by a prodromal of fever followed by an eruption of painful, ulcerative lesions of the gingiva and mucosa, and often, perioral, vesicular lesions. Purpose: The case reported management of acute primary herpetic gingiva-stomatitis in a 6 years old boy. Case: A 6-year-old boy with complaints of difficulty eating or drinking due to pain associated with multiple ulcers in the oral cavity and lips. Patient have been living in boarding school since 6 months ago and was complained of stomatitis which have occurred 4 days ago followed by fever and malaise. Case Management: The patient was instructed to eat nutritious (high calorie and protein diet), soft, blend diet and the following medications were prescribed: (1) antiviral drug (Acyclovir® tablet 200mg) for four times a day; (2) topical hyaluronic acid gel (Aloclair® gel 8ml) to be applied on lesions; (3) mouthwash containing benzydamine hydrochloride (Tantum Verde® 15ml) for three times a day; and (4) multivitamin syrup for three times a day. Conclusion: The case reported that the drugs treatment was used according to the severity of HSV-1 infection and patient's symptoms of acute primary herpetic gingiva-stomatitis. Providing supportive care and educating about transmission of the virus are important aspects of nursing care.